The Evolution of Green Consumer Behaviour in the Digital Era: A Systematic Review and Research Agenda - Purnama, Nadia Tsabita (Generate Digital Publishing, 2025)
Objective: This study aims to systematically review andmap the evolution of green consumer behavior in the digital age byintegrating perspectives on sustainability, marketing, and information technology.This study seeks to identify the main themes, theoretical approaches, andnew research trends that shape the transformation of sustainable consumption behaviorin the digital context. Research Design & Methods: This study applied a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol. Data search was conducted through the Scopus database for the period 2010–2025 in the fields of Business, Management, and Accounting. Of the total 2,804 documents identified, 124 articles met the initial synthesis stage, and 36 final articles were analyzed qualitatively using thematic clustering to identify conceptual patterns related to digital engagement, green marketing strategies, and ethical consumption behavior. Findings: The results identified four main clusters: (1) Green Trust and Digital Authenticity, which highlights the importance of transparency and credibility in sustainability communication; (2) AI, Personalization, and Sustainable Engagement, which emphasizes the role of algorithms and artificial intelligence in environmentally friendly decisions; (3) Digital Influencers and Green Socialization, which explains the influence of social media on pro-environmental identities; and (4) Ethical Consumption and Green Identity, which focuses on the moral and symbolic dimensions of sustainability. The analysis also shows a methodological shift towards data-driven sustainability and a cross-cultural approach in understanding digital green consumer behavior. Implications & Recommendations: These findings provide strategic insights for policymakers and practitioners to design an ethical digital marketing framework, promote algorithmic transparency, and strengthen sustainability-oriented digital literacy. Further research is recommended using longitudinal and cross-cultural approaches to explore the dimensions of digital ethics, trust in AI, and emotional relationships in the formation of consumer green identity. Contribution & Value Added: This article contributes to integrating behavioral, technological, and ethical theories in explaining the evolution of green consumer behavior. Theoretically, this research expands understanding by linking the Theory of Planned Behavior (TPB) with digital-era constructs such as AI-based trust and authentic sustainability communication.